2016
DOI: 10.1002/ange.201610665
|View full text |Cite
|
Sign up to set email alerts
|

Development of Gold‐catalyzed [4+1] and [2+2+1]/[4+2] Annulations between Propiolate Derivatives and Isoxazoles

Abstract: Tw on ew gold-catalyzed annulations of isoxazoles with propiolates have been developed. Most isoxazoles follow an initial Oattackonthe alkyne to afforda[4+ +1] annulation product. This process results in ar emarkable alkyne cleavage of initial propiolates.U nsubstituted isoxazoles proceed through an Nattacks tep to yield formal [2+ +2+ +1]/[4+ +2] annulation products.T hese two annulation products arise initially from two seven-membered heterocyclic intermediates, which then lead to products.Supportinginformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 61 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…In addition, Liu and co-workers described an elegant goldcatalysed chemoselective annulation of electron-deficient alkynes 134 with anthranils to yield quinolone oxides (Scheme 50). 65 This annulation was compatible with substrates over a wide scope. It was found that the electron density of ligands has a significant impact on the chemoselectivity of this reaction.…”
Section: Formal [4 + 2] Cycloaddition Of Anthranilsmentioning
confidence: 85%
“…In addition, Liu and co-workers described an elegant goldcatalysed chemoselective annulation of electron-deficient alkynes 134 with anthranils to yield quinolone oxides (Scheme 50). 65 This annulation was compatible with substrates over a wide scope. It was found that the electron density of ligands has a significant impact on the chemoselectivity of this reaction.…”
Section: Formal [4 + 2] Cycloaddition Of Anthranilsmentioning
confidence: 85%
“…They have reported two kinds of annulations of isoxazoles with ynones to afford pyrroles 107.7 [Eq. (107‐1)] and imidazopyridines 107.8 [Eq.…”
Section: Oxygen‐containing Nucleophilesmentioning
confidence: 99%
“…(108‐2)]. It should be emphasized that an initial N‐attack of the 1,2‐benzisoxazole at the alkyne and an ester attack at the iminium moiety formed heterocyclic intermediates 108.1 and 108.7 , which are much different from those in the previous reaction . For species 108.5 , loss of the tert ‐butyl cation led to 108.11 [Eq.…”
Section: Oxygen‐containing Nucleophilesmentioning
confidence: 99%
“…1 Their analogues have been successfully used for pharmaceutical chemistry as well as in materials science. 2 Marketed drugs like alpidem, 3 zolpidem, 4 nicopidem and saripidem, 5 minodronic acid, 6 and optically active GSK812397 drug 7 are derived from the imidazo[1,2- a ]pyridine scaffold (Figure 1). 8…”
Section: Introductionmentioning
confidence: 99%